This preview shows page 1. Sign up to view the full content.
Unformatted text preview: F x = 3 F . Now, bead 3 exerts a leftward force of magnitude F on the central bead, while bead 1 exerts a rightward force of magnitude F . Therefore, F F = 3 F . F = ( 3 + 1) F . The fact that Coulombs law depends inversely on distancesquared then implies r 2 = d 2 3 + 1 r = d 3 + 1 = 10 cm 10 cm 1.65 3 1 = = + 6.05 cm where r is the distance between bead 1 and the central bead. This corresponds to 6.05 cm . x = (b) To regain the condition of high symmetry (in particular, the cancellation of xcomponents) bead 3 must be moved closer to the central bead so that it, too, is the distance r (as calculated in part(a)) away from it....
View
Full
Document
 Spring '08
 Any
 Physics, Force

Click to edit the document details